Mappadendang: Ekspresi Rasa Syukur Oleh Masyarakat Petani di Atakka Kabupaten Soppeng - Abdul Rahman; Mauliadi Ramli (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the ritual process and the meaning and values ​​contained in the traditional mappadendang party. In this study using descriptive qualitative research methods, namely research that describes situations directly in the research place. Meanwhile, the data collection techniques used were observation, interviews, and documentation. The results of the study indicate that the process of the traditional mappadendang party ritual in Soppeng Regency is very structured and neatly arranged. Starting from determining the day of implementation and the duration or length of time for implementation. After the process of determining the time is complete, the family who will carry out the traditional party begins to arrange the arrangement of the mappadendang traditional party. For example, entertainment events and players who will pound the pestle on the mortar and the attributes used by players at the traditional party. The traditional party ended with a marked meal together by all the people who attended the traditional party. In the traditional mappadendang party there are meanings and values ​​contained in it, these meanings are applied in the form of actions such as gratitude to God and respecting and preserving the heritage of ancestors or ancestors. Likewise with the values ​​contained in the traditional mappadendang party, the values ​​of togetherness, kinship, entertainment, and religion are merged into one in a traditional party that continues to be preserved and becomes a way of life for the community.